Features of management of receivables - Nurseitov А.А.; Sadvokasova , F.B. (BUKETOV BUSINESS REVIEW, 2018)
Current assets serve as an integral part of the continuous cyclical process of reproduction for companies. The shortage or inefficient use of working capital can lead to a slowdown in their turnover, which leads to a decrease in the solvency and financial stability of the company, and ultimately - to financial insolvency and even bankruptcy. Therefore, for an uninterrupted financial and economic activity, companies need proper management of working capital. To manage current assets, companies develop and use their own policies, which can be aggressive, moderate or conservative. One of the key elements of current assets is accounts receivable (DZ), for which a special management policy is required. The lack of a full-fledged picture of the data on the effectiveness of investing in the DZ leads to the management of the situation on the principle of «extinguishing the fire.» Therefore, information serves as the most important element underlying the entire RC management system. The authors recommend that companies determine the optimal ratio between receivables and payable in order to obtain the greatest benefits and the least losses in the implementation of the strategy. In their view, to effectively manage the DZ, the company must formulate a set of rules governing the processes of granting credit and cash collection.